VISUALIZATION AND REALITY IN PACKAGED BEVARAGE ADVERTISING - Setyawan, Denny Hendrifika (Seni Media Rekam ISI Surakarta, 2023)
Visual and audio advertising media as information broadcast to audiences must consider advertising ethics because bombastic and manipulative visualizations and narrative sentences deceive the public by providing untruthful information. According to advertising ethics, ontology, and epistemology studies, revising the media’s presentation of product advertisements is imperative. Accordingly, this study utilizes a descriptive-quantitative method based on previous studies and direct observation of the